Membangun Kesadaran untuk Belajar Hingga Perguruan Tinggi di SMK Mambail Futuh, Jenu, Tuban - Bambang Minto Basuki (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2026)
The low level of awareness among vocational high school (SMK) students to continue their education to higher education remains a major issue, particularly at SMK Mambail Futuh, Jenu District, Tuban Regency. Economic constraints, limited access to information, and an orientation toward immediate employment are dominant factors influencing students’ decisions. This community service activity aims to build students’ awareness and motivation regarding the importance of higher education as a long-term investment. The implementation method includes educational socialization, interactive discussions, the presentation of inspirational experiences, and the introduction of higher education admission pathways and financing schemes. The results show an improvement in students’ understanding of the benefits of higher education and a growing interest in pursuing further studies after graduation. This activity emphasizes that communicative and contextual educational approaches play a crucial role in encouraging positive mindset changes among SMK students toward higher education.